. Поменяйте знак в знаменателе одной из дробей и перед этой дробью, а за- тем упростите выражение: б) 2a - 3b/a-b - 3b/b-a =
в)x²-48/x-8 + 16/8-x =
г) a²/a-4 + 16/4-a =

olyamin0 olyamin0    3   17.10.2021 12:03    0

Ответы
fariza34 fariza34  30.11.2021 02:01

Объяснение:

b)\ \frac{2a-3b}{a-b}-\frac{3b}{b-a}=\frac{2a-3b}{a-b}+\frac{3b}{a-b}=\frac{2a-3b+3b}{a-b} =\frac{2a}{a-b}.\\c)\ \frac{x^2-48}{x-8}+ \frac{16}{8-x} =\frac{x^2-48}{x-8}-\frac{16}{x-8} =\frac{x^2-48-16}{x-8} =\frac{x^2-64}{x-8} =\frac{(x-8)(x+8)}{x-8} =x+8.\\d)\ \frac{a^2}{a-4}+\frac{16}{4-a}=\frac{a^2}{a-4}-\frac{16}{a-4}=\frac{a^2-16}{a-4} =\frac{(a-4)(a+4)}{a-4} =a+4.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра